Peran Guru Pendidikan Agama Katolik Dalam Pendidikan Iman Dan Karakter Anak Di Sekolah - Linda Linda; Intansakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The role of the teacher is a person who occupies a position and plays an important role in the world of education. Teachers act as mentors in their duties, namely educating. Catholic religious teachers in their duties and roles carry out multiple missions, namely as preachers and educators. As a preacher, a Catholic religious teacher takes part of the prophetic task of proclaiming the news of God's Salvation. While as an educator, the task of PAK teachers is to lead students to maturity both physical maturity and spiritual maturity. the research used in this study is descriptive qualitative, with the aim of analyzing how the role of PAK in the education of faith and character of children at school with data analysis techniques using the Miles and Huberman model. The emphasis of Catholic religious teacher education leads to three aspects, namely knowledge, skills, and attitudes that occur in the teaching and learning process systematically. So that character education is expected to be able to form a generation whose existence provides the widest possible benefit to the surrounding environment. Character education in essence is to form a nation that is resilient, competitive, noble, moral, tolerant, mutual cooperation, political spirit, dynamically developing, science and technology oriented, all of which are imbued with faith and piety to God Almighty based on Pancasila.